2007
DOI: 10.1111/j.1463-1318.2007.01265.x
|View full text |Cite
|
Sign up to set email alerts
|

A 6‐year review of surgical morbidity and oncological outcome after high anterior resection for colorectal malignancy with and without splenic flexure mobilization

Abstract: No morbidity, oncological or survival disadvantage in performing splenic flexure preserving HAR was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 16 publications
2
30
2
Order By: Relevance
“…In general, the global, clinical judgement seems to localize a subset of patients at risk for developing complications in general, whereas many patients with no risk factors at all may develop anastomotic leakage [12]. The risk factors for anastomotic leakage identified by univariate and multivariate analysis in our study corroborate with those found in other studies [1][2][3][4][5][6][7][8]. Similar to these studies, the number of risk factors present in an individual patient appeared to be an important predictor of anastomotic leakage in all anastomoses.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In general, the global, clinical judgement seems to localize a subset of patients at risk for developing complications in general, whereas many patients with no risk factors at all may develop anastomotic leakage [12]. The risk factors for anastomotic leakage identified by univariate and multivariate analysis in our study corroborate with those found in other studies [1][2][3][4][5][6][7][8]. Similar to these studies, the number of risk factors present in an individual patient appeared to be an important predictor of anastomotic leakage in all anastomoses.…”
Section: Discussionsupporting
confidence: 88%
“…Clinically relevant anastomotic leakage rates range between 3% and 19% [1,[3][4][5][6][7][8][9]. Anastomotic leakage may remain localized, causing perianastomotic inflammation or abscess formation, or may progress to generalised peritonitis.…”
Section: Introductionmentioning
confidence: 99%
“…[4] who analysed the results of 707 open HARs, of which 531 (75%) were deemed at surgery to require SFM. Drawing the evidence together, routine mobilization of the splenic flexure during open anterior resection should probably be abandoned in favour of a selective approach.…”
mentioning
confidence: 99%
“…The right lateral approach for laparoscopic SFM was recently introduced to ensure a safe, rapid and complete mobilization of the splenic flexure . Some surgeons recommend that SFM should be performed only when there is tension at the anastomosis . While we agree with this recommendation, our policy is that SFM is a routine step during low anterior resection because it requires only 15–20 min more operation time than not performing it.…”
Section: Discussionmentioning
confidence: 88%